The Analysis of Oppression in Earth’s Answer by William Blake - Martina Girsang; David Chandra; Sari Ayu Pinem; Widya Wati Wijaya; Jenny Tanato (Departement of Mathematics Education, 2024)
In this research, the researchers will conduct an analysis of “Earth’s Answer” by William Blake. The purpose of this research is to explore the sense of oppression in the content of the poem. The method utilized for this study is a qualitative descriptive method. The main focus of the research is the indications of oppression found in the poem, through symbols used by Blake, which examined stanza by stanza. Researchers found that the signs of oppression from the poem are taken from the words such as “prisoned,” “chained,” “darkness,” “dread,” and “drear.” By analyzing the background of the author, major theme, poetic devices, literary devices, and also examined each stanza of the poetry, it can be concluded that this poetry involves the subject of oppression. The results underscore the absence of hope, injustice, and incarceration, due to one of the impacts of the Industrial Revolution, as well as other oppressive elements found in the poem. The idea of oppression can be found in each stanza either explicitly or implicitly.